Recurrent pregnancy loss: current perspectives - El Hachem H; Crepaux V; May-Panloup P; Descamps P; Legendre G; Bouet PE (Dove Medical Press, 2017)
Hady El Hachem,1,2 Vincent Crepaux,3 Pascale May-Panloup,4 Philippe Descamps,3 Guillaume Legendre,3 Pierre-Emmanuel Bouet3 1Department of Reproductive Medicine, Ovo Clinic, Montréal, QC, Canada; 2Department of Obstetrics and Gynecology, University of Montreal, Montréal, QC, Canada; 3Department of Obstetrics and Gynecology, Angers University Hopsital, Angers, France; 4Department of Reproductive Biology, Angers University Hospital, Angers, France Abstract: Recurrent pregnancy loss is an important reproductive health issue, affecting 2%–5% of couples. Common established causes include uterine anomalies, antiphospholipid syndrome, hormonal and metabolic disorders, and cytogenetic abnormalities. Other etiologies have been proposed but are still considered controversial, such as chronic endometritis, inherited thrombophilias, luteal phase deficiency, and high sperm DNA fragmentation levels. Over the years, evidence-based treatments such as surgical correction of uterine anomalies or aspirin and heparin for antiphospholipid syndrome have improved the outcomes for couples with recurrent pregnancy loss. However, almost half of the cases remain unexplained and are empirically treated using progesterone supplementation, anticoagulation, and/or immunomodulatory treatments. Regardless of the cause, the long-term prognosis of couples with recurrent pregnancy loss is good, and most eventually achieve a healthy live birth. However, multiple pregnancy losses can have a significant psychological toll on affected couples, and many efforts are being made to improve treatments and decrease the time needed to achieve a successful pregnancy. This article reviews the established and controversial etiologies, and the recommended therapeutic strategies, with a special focus on unexplained recurrent pregnancy losses and the empiric treatments used nowadays. It also discusses the current role of preimplantation genetic testing in the management of recurrent pregnancy loss. Keywords: recurrent pregnancy loss, recurrent miscarriage, antiphospholipid syndrome, preimplantation genetic screening, preimplantation genetic diagnosis